2008
DOI: 10.1021/jf8008553
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compound Concentration and Antioxidant Activities of Edible and Medicinal Mushrooms from Korea

Abstract: A study was conducted to determine the content of phenolic compounds and the antioxidative activity of five edible and five medicinal mushrooms commonly cultivated in Korea. Phenolic compounds were analyzed using high performance liquid chromatography, and antioxidant activity was evaluated by 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity and superoxide dismutase activity. A total of 28 phenolic compounds were detected in the mushrooms studied. The average total concentration of phenolic compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
217
4
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(278 citation statements)
references
References 22 publications
21
217
4
18
Order By: Relevance
“…The studied sample of G. lucidum fruiting body revealed higher reducing power than a sample from Taiwan (~50% at 0.75 mg/ml; Mau et al, 2002) and higher DPPH scavenging activity than samples from Korea (~74% at 10 mg/ml; Kim et al, 2008) and from Taiwan (~50% at 0.5 mg/ml; Mau et al, 2002). Furthermore, the antioxidant activity of mycelium ethanolic extract of G. lucidum from Central Italy was previously reported (Saltarelli et al, 2009), and the EC 50 value for DPPH scavenging activity (~0.3 mg/ml; mycelium obtained in PDA culture medium) was lower than the one reported in the present study (0.90 mg/ml).…”
Section: Evaluation Of Antioxidant Activitymentioning
confidence: 73%
See 2 more Smart Citations
“…The studied sample of G. lucidum fruiting body revealed higher reducing power than a sample from Taiwan (~50% at 0.75 mg/ml; Mau et al, 2002) and higher DPPH scavenging activity than samples from Korea (~74% at 10 mg/ml; Kim et al, 2008) and from Taiwan (~50% at 0.5 mg/ml; Mau et al, 2002). Furthermore, the antioxidant activity of mycelium ethanolic extract of G. lucidum from Central Italy was previously reported (Saltarelli et al, 2009), and the EC 50 value for DPPH scavenging activity (~0.3 mg/ml; mycelium obtained in PDA culture medium) was lower than the one reported in the present study (0.90 mg/ml).…”
Section: Evaluation Of Antioxidant Activitymentioning
confidence: 73%
“…The fruiting body (FBPh) revealed the highest total amount (1.23 mg/100 g dw, dry weight), while the mycelium obtained in liquid MMN culture medium (M-lMMN-Ph) provided the lowest concentration (0.25 mg/100 g dw). Kim et al (2008) reported a higher amount of phenolic compounds in a sample of G. lucidum from Korea (16.2 mg/100 g dw), as also the presence of different phenolic compounds, such as other phenolic acids and derivatives (gallic acid, protocatechuic acid, 5-sulfosalicylic acid and pyrogallol), flavan-3-ols (catechin), flavanones (naringin and hesperetin), flavonols (myricetin, quercetin and kaempherol), and isoflavones (formononetin and biochanin A). The absence of these compounds in the sample herein studied was confirmed using mass spectrometry (MS).…”
Section: Characterization Of Phenolic Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Woldegiorgis et al [7] detected in P. ostreatus caffeic, gallic and p-hydroxybenzoic acids and myricetin. Kim et al [59] additionally quantified homogentisic, protocatechuic, chlorogenic acids, naringin and myricetin. The study of P. ostreatus by Palacios et al [5] confirmed p-coumaric, ferulic, gallic, gentisic, p-hydroxybenzoic, homogentisic and protocatechuic acids and myricetin in fruiting bodies.…”
Section: Chromatographic Profilementioning
confidence: 99%
“…The study of P. ostreatus by Palacios et al [5] confirmed p-coumaric, ferulic, gallic, gentisic, p-hydroxybenzoic, homogentisic and protocatechuic acids and myricetin in fruiting bodies. Kim [6,7,59]. Flavonoids or their aglycones (myricetin, quercetin, naringenin, kaempferol and hesperetin) were also detected in different species of edible mushroom [5,7,59] (although neither fungi nor animals, but only plants have the ability to biosynthesize flavonoids [60]).…”
Section: Chromatographic Profilementioning
confidence: 99%